FAKTOR- FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI LABKESDA KABUPATEN LEBAK - Yumhi Yumhi; Ida Farida; Agung Agung (The Asia Pacific Journal Of Management Studies, 2022)
This study intends to find out the interrelationships of the factors that affect the performance of the Labkesda employees of Lebak Regency. There are many variables that might influence, but only Locus Of Control, Compensation, and Job Satisfaction were selected. The research method used is a quantitative survey method with causality studies with 56 sample data using the random sample technique, while the analysis used is correlation and regression analysis. The results prove that there is an effect of locus of control on job performance, there is an effect of compensation on job performance, there is an effect of job satisfaction on job performance, there is an effect of locus of control, compensation and job satisfaction together on job performance. These findings indicate that the Lebak Regency Labkesda organization should pay attention to and encourage locus of control, compensation and job satisfaction to continue to be improved.